2012
DOI: 10.1038/ng.2251
|View full text |Cite|
|
Sign up to set email alerts
|

A genome-wide association study identifies susceptibility loci for Wilms tumor

Abstract: Wilms tumor is the most common renal malignancy of childhood. To identify common variants that confer susceptibility to Wilms tumor we conducted a genome-wide association study in 757 cases and 1,879 controls. We evaluated ten SNPs in regions significant at P<5×10−5 in two independent replication series from the UK (769 cases and 2,814 controls) and the US (719 cases and 1,037 controls). We identified clear significant associations at two loci, 2p24 (rs3755132, P=1.03×10−14 and rs807624, P=1.32×10−14) and 11q1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 14 publications
1
57
0
Order By: Relevance
“…Recently, a similar region of germline gain encompassing both genes was detected in a patient with bilateral nephroblastomatosis and a family history of WT [39]. A genome-wide association study has also identified potential WT susceptibility loci in this commonly gained region, mapping to SNPs that flank DDX1 [40]. We cannot therefore rule out a significant role for DDX1 in Wilms tumour.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a similar region of germline gain encompassing both genes was detected in a patient with bilateral nephroblastomatosis and a family history of WT [39]. A genome-wide association study has also identified potential WT susceptibility loci in this commonly gained region, mapping to SNPs that flank DDX1 [40]. We cannot therefore rule out a significant role for DDX1 in Wilms tumour.…”
Section: Discussionmentioning
confidence: 97%
“…Point mutations in WT1, WTX, b-catenin, and abnormalities involving translocations in chromosome 6 have been linked to Wilms tumor (Knudson and Strong 1972;Rivera and Haber 2005;Hu et al 2011), and several susceptibility loci for Wilms tumor were recently identified by a genome-wide association study (Turnbull et al 2012). However, the underlying genetic basis of most cases of Wilms tumor remains unknown (Turnbull et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying genetic basis of most cases of Wilms tumor remains unknown (Turnbull et al 2012). Here we report that up to a third of human Wilms tumors overexpress LIN28B.…”
Section: Discussionmentioning
confidence: 99%
“…This requires large sample sizes not readily achievable for rare diseases. Yet, despite the a priori presumption that the GWAS design could not be successfully applied to childhood cancers investigations of ALL(58-64), neuroblastoma(65-74), Wilm's tumor(75), osteosarcoma(76), and Ewing's sarcoma (77), each have identified multiple variants associated with each disease (Table 2). The unexpected success of GWAS to studies of these rare cancers appears to be due to the larger magnitude of SNV-disease association among young onset cancers compared to those with adult onset, which was recently formally quantified (Figure 4) (78).…”
Section: Introductionmentioning
confidence: 99%